Identification of Multimodel LPV Models with Asymmetric Gaussian Weighting Function. (16th December 2013) - You, Jie; Lu, Jiangang; Zhu, Yucai; Yang, Qinmin; Zhu, Jianhua; Huang, Jiangyin; Sun, Youxian
Abstract : This paper is concerned with the identification of linear parameter varying (LPV) systems by utilizing a multimodel structure. To improve the approximation capability of the LPV model, asymmetric Gaussian weighting functions are introduced and compared with commonly used symmetric Gaussian functions. By this mean, locations of operating points can be selected freely. It has been demonstrated through simulations with a high purity distillation column that the identified models provide more satisfactory approximation. Moreover, an experiment is performed on real HVAC (heating, ventilation, and air-conditioning) to further validate the effectiveness of the proposed approach.